Perfil Epidemiologico das Vitimas de Traumatismo Cranio-Encefalico - Oliveira, Patricia Alves de (2004)
The trauma has been assuming great epidemic proportions, causing several deaths in al of the ages, just tosing for the cardiovascular diseases and cancer. For that reason, he/she became a problem of public health, that besides the death, he/she leaves significant sequels and it reduces a productive labor. Among the several traumas that ca be unchained by accidents and/or violence have the cranial traumas, which are accompanied of complications that interfere in the quality of the victims´ life per times. This study had as objective knows the victims´of traumatism cranioencefalico epidemic profile admited at an emergency hospital. It is a study of exploratory-descriptive character, developed at a public hospital of emergency, located in the city of Fortaleza. The data were collected in the period of march to april of 2004, with a sample of 770 internal people with trauma cranioencefalico. After collection the data were exposed in tables for subsequent analysis. As result had that most of the victims (83,1%) it belongs to the masculine sex, in the age group from 21 to 30 years (23,9%); the main day of occurence was on Sunday (20,5%), staying a medium period of internamento of up to 07 days (49,7%) and the main cause was the motorcycle accident (27%). Starting from this study we noticed the nurse´s importance more and more to be inserted in the prevention context to the accidents, as a consequence of the current complications of these. It is interesting if thinks in an addressed protocol the systematic evaluation to the neurological patients and to apply the systemization of the nursing attendance to this group.Key-words: trauma cranioencefalico, accidents, epidemiology.